2012
DOI: 10.1038/ijo.2012.174
|View full text |Cite
|
Sign up to set email alerts
|

Food cues and ghrelin recruit the same neuronal circuitry

Abstract: This study reveals a role for ghrelin, but not leptin, signaling within medial hypothalamus in FAA on both a population level and in single cells, identifying a subset of neurons onto which cue information and ghrelin signaling converge, possibly to drive FAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 62 publications
2
13
0
Order By: Relevance
“…A previous study has identified ghrelin signaling within the medial hypothalamus as a potential node in the network that regulates FAA. 61 In agreement with this, GHS-R1a knockdown induced a reduction in FAA amplitude in the DMH, and a delay in onset of FAA in VMH as well as DMH. Together, this implicates mediobasal hypothalamic GHS-R1a signaling as an important part of the network that regulates FAA.…”
Section: Discussionsupporting
confidence: 65%
“…A previous study has identified ghrelin signaling within the medial hypothalamus as a potential node in the network that regulates FAA. 61 In agreement with this, GHS-R1a knockdown induced a reduction in FAA amplitude in the DMH, and a delay in onset of FAA in VMH as well as DMH. Together, this implicates mediobasal hypothalamic GHS-R1a signaling as an important part of the network that regulates FAA.…”
Section: Discussionsupporting
confidence: 65%
“…“Hedonic overdrive” has been recently proposed as an explanation for overeating in humans (Cohen, 2008 ; Berridge and Kringelbach, 2011 ; van der Plasse et al, 2013 ). Briefly, the high reward salience of certain foods leads to their consumption even in states of satiety and/or sufficient energy reserves.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments in mice have demonstrated that ghrelin appears to work as an output of a FEO that is located in the oxyntic cells of the stomach (LeSauter et al 2009, Laermans et al 2015. Furthermore, FAA is significantly reduced in rodents that lack ghrelin receptors (LeSauter et al 2009), and systemic administration of ghrelin activates a subset of specific neurons in the medial hypothalamus during FAA ( Van der Plasse et al 2013). Ghrelin also induces phase advances in the electrical activity of neurons in mouse SCN explants and promotes a phase advance in the rhythm of per2 expression, suggesting that it affects the SCN clockwork (Yannielli et al 2007).…”
Section: Ghrelinmentioning
confidence: 99%